Experience of stereotactic radiation therapy and radiosurgical treatment of metastatic vertebral tumors - O. I. Kit; D. E. Zakondyrin; E. E. Rostorguev; P. G. Sakun; V. I. Voshedskii; M. A. Komandirov (Южно-Российский онкологический журнал)
Purpose of the study. Evaluation of the effectiveness of extracranial stereotactic radiation therapy in various fractionation regimens in the treatment of patients with metastatic vertebral lesions.Patients and methods. The study included 12 patients with metastatic spinal lesions who underwent extracranial stereotactic radiation therapy (SBRT) on a Novalis Tx linear accelerator, Varian, in radiosurgery mode (SRS; in 1 fraction) and hypofractionation mode (SFD 5Gy, TFD 25Gy, 5 fractions) in the period from 01/01/2020 to 03/31/2022. The assessment of local control was carried out using positron emission tomography – computed tomography (PET-CT) from 18FDG. The intensity of the pain syndrome before and after radiation was assessed using a visual analog pain scale (VAS).Results. 19 vertebrae with metastatic lesions were irradiated in 12 patients. The SBRT technique in hypofractionation mode was used in 6 (50 %) patients, in radiosurgery (SRS) mode was used in 4 (34 %) patients, in 2 (17 %) patients a combination of irradiation techniques was used on various affected segments of the spinal column. The general tumor volume (GTV) averaged 30.56 = 7.8 km2. When using the radiosurgical irradiation regimen, SFD ranged from 16 to 18 Gy. When using the hypofractionation technique, the total focal dose (TFD) was 25 Gy, a single focal dose (SFD) was 5 Gy.Conclusion. Stereotactic radiation therapy and radiosurgery of metastatic vertebral tumors without compression of neural structures provides local tumor control in 92 % of patients within 6 months and in 83 % of patients within 1 year, regression of pain after irradiation – in 67 % of patients.